2002
DOI: 10.1017/s0033291702005299
|View full text |Cite
|
Sign up to set email alerts
|

Home treatment for mental health problems: a systematic review

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
13

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 228 publications
2
63
0
13
Order By: Relevance
“…Our findings provide evidence to support most previous studies, [5][6][7][8][9][10]12,13 which demonstrated that CRHT teams reduce admission rates and reduce length of in-patient stay. Tyrer et al 11 found a non-significant reduction of 7.7% in admissions following the introduction of a CRHT in Cardiff, but they examined a control population in which they found the same reduction of 7.7% in admissions, which they acknowledge consisted of a population so dissimilar in size and socioeconomic circumstances that it was effectively incomparable with the test group.…”
Section: Contextsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings provide evidence to support most previous studies, [5][6][7][8][9][10]12,13 which demonstrated that CRHT teams reduce admission rates and reduce length of in-patient stay. Tyrer et al 11 found a non-significant reduction of 7.7% in admissions following the introduction of a CRHT in Cardiff, but they examined a control population in which they found the same reduction of 7.7% in admissions, which they acknowledge consisted of a population so dissimilar in size and socioeconomic circumstances that it was effectively incomparable with the test group.…”
Section: Contextsupporting
confidence: 90%
“…6,7 A number of investigations have also showed reduced length of in-patient stay following introduction of CRHT. [8][9][10] Crisis resolution and home treatment teams have now been implemented throughout England and Wales. Jethwa et al 7 performed an evaluation of the long-term effects of the introduction of CRHT in Leeds and demonstrated a significant reduction in admission rates of 37.5% in the first year.…”
mentioning
confidence: 99%
“…Thus, this activity contributes to decrease the demand for specialized services of mental health and reduce the hospitalization rates (23) .…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, Catty et al's (2002) systematic review of randomised controlled trials of home-based treatment found that two service components were associated with greater efficacy of home treatment teams when compared with other community services, including out-patient clinics: integration of health and social care responsibilities, and regular home visiting, both of which are consistent components of modern multidisciplinary CMHTs in the UK.…”
Section: Box 1 How To Respond To a Missed Appointmentmentioning
confidence: 90%